Drug- and Cell-Type-Specific Effects of ROCK Inhibitors as a Potential Cause of Reticular Corneal Epithelial Edema - Schlötzer-Schrehardt, Ursula; Gießl, Andreas; Zenkel, Matthias; Bartsch, Alexander; Okumura, Naoki; Koizumi, Noriko; Kinoshita, Shigeru; Tourtas, Theofilos; Kruse, Friedrich (Cells, 2025)
Rho-associated kinase (ROCK) inhibitors have gained popularity as novel treatment options in the management of glaucoma and corneal endothelial disorders. Among the various ocular side effects, reticular corneal epithelial edema has been most frequently reported, mainly after treatment with netarsudil. To explain the potential mechanisms, we comparatively analyzed the effects of ripasudil and netarsudil on corneal endothelial and epithelial function in vitro. Primary human corneal endothelial and epithelial cells were incubated with netarsudil dihydrochloride and ripasudil hydrochloride dihydrate for up to 7 days. Gene and protein expression analyses were performed by real-time PCR and immunocytochemistry. Functional assays assessed the cell migration, proliferation, viability, Na+/K+-ATPase activity, transcellular electrical resistance, and FITC–dextran permeability. Reticular bullous corneal epithelial edema was observed in a patient following netarsudil 0.02%/latanoprost 0.005% ophthalmic solution (Roclanda®) for elevated intraocular pressure. In the subsequent laboratory analyses, both netarsudil and ripasudil were found to improve the corneal endothelial pump and barrier function, but they showed differential effects on corneal epithelial cells. Whereas ripasudil improved the epithelial barrier function by upregulating major components of the tight and adherens junctions and reducing paracellular permeability, netarsudil had no or even adverse effects on the epithelial barrier properties by downregulating the expression levels of cell-junction-associated genes. The expression changes normalized after discontinuation of ROCK inhibitors. The findings support the concept that ROCK inhibitors can act as a double-edged sword by having beneficial effects on corneal endothelial cells and adverse effects on epithelial cells.
CRIS-Team Scopus Importer:2025-03-14
Keywords: corneal endothelium; corneal epithelium; honeycomb epithelial edema; netarsudil; reticular bullous corneal epithelial edema; Rho kinase inhibitor; ripasudil; ROCK inhibitor